2016
DOI: 10.1007/s11469-016-9666-2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Gaming Machine Characteristics: It’s the Little Things That Count

Abstract: A range of gamblers, from low-frequency social gamblers through to problem gamblers in treatment, participated in focus groups discussing the characteristics of Electronic Gaming Machines (EGMs) that they found attractive. Analyses of the resulting transcripts resulted in two groups of EGM characteristics being identified as important, one group associated with winning and one with betting. Overall, free spin features were identified in all groups as the most attractive characteristic of EGMS. Beyond that it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
3
20
2
Order By: Relevance
“…Considering the potential effects across a range of EGM characteristics, Landon et al [101] conducted a focus group study in New Zealand exploring which characteristics participants found attractive. Free spin features were the most attractive.…”
Section: Electronic Gaming Machinesmentioning
confidence: 99%
“…Considering the potential effects across a range of EGM characteristics, Landon et al [101] conducted a focus group study in New Zealand exploring which characteristics participants found attractive. Free spin features were the most attractive.…”
Section: Electronic Gaming Machinesmentioning
confidence: 99%
“…Despite this change, many online casino products are still without limits on either stakes or speed of play. Changes to such "structural characteristics" of gambling games have a potential to reduce gambling expenditure (Cornish, 1978;Landon et al, 2018;Livingstone, Woolley, Zazryn, Bakacs, & Shami, 2008), and consequently gambling-related harm (Browne et al, 2016;Markham, Young, & Doran, 2016;Muggleton et al, 2021). Indeed, the maximum stake on UK electronic gambling machines (EGMs) was brought down from £100 to £2 in 2019 (Casey, 2018) and gambling expenditure on this product has subsequently fallen by almost 50% (Witherow, 2020).…”
mentioning
confidence: 99%
“…Overall possible that own gambling is underreported, but no reason to question honesty of participants. It is noteworthy that no participants described any positive views on gambling, which is rare for those gambling, even problem gamblers (see e.g., Landon, Palmer du Preez, Page, Bellringer, Roberts, & Abbott., 2016).…”
Section: Discussionmentioning
confidence: 99%